NEURAL NETWORK SYNCHRONIZATION AS A MARKER OF DISEASE PROGRESSION (Global Conference on Medical and Health Sciences, 2026)
Neural network synchronization plays a fundamental role in brain function, enabling coordinated communication between distributed neuronal populations. Alterations in synchronization dynamics have been increasingly recognized as key features of neurological and neurodegenerative disorders, reflecting disruptions in functional connectivity and network organization. Abnormal synchronization patterns have been observed in conditions such as epilepsy, Parkinson’s disease, Alzheimer’s disease, and multiple sclerosis, suggesting their potential utility as biomarkers of disease progression.
Keywords: Neural synchronization; Brain networks; Phase coupling; Coherence; EEG; Functional connectivity; Disease progression; Neurodegeneration